SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166177-ms
|View full text |Cite
|
Sign up to set email alerts
|

Completion and Production Strategies for Liquids-Rich Wells in Ultra-low-permeability Reservoirs

Abstract: Producing from liquids-rich, ultra-low-permeability reservoirs requires long, horizontal wells with multiple fractures—a situation that demands a better understanding of well-completion practices in relation to reservoir dynamics to maximize benefit. This paper attempts to augment that understanding through a stochastic reservoir modeling approach. A reservoir simulation model for a typical condensate well in the Eagle Ford liquids-rich area was used in a decision-under-uncertainty framework to identify optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…For the cases studied, a one-year delay did not result in a significant loss of five-year cumulative oil or gas production, except for the cases in which the created fractures for the well placed later had shorter half-lengths than the original wells. • Placing the well at the location with highest CGR and highest matrix permeability always resulted in higher production, and this does not contradict the single-well sensitivity observations by Kumar et al (2013) and Dahl et al (2014). • This study also showed that much higher cumulative production of oil and gas can be obtained by increasing the vertical height of the fractures.…”
Section: Observationssupporting
confidence: 55%
See 1 more Smart Citation
“…For the cases studied, a one-year delay did not result in a significant loss of five-year cumulative oil or gas production, except for the cases in which the created fractures for the well placed later had shorter half-lengths than the original wells. • Placing the well at the location with highest CGR and highest matrix permeability always resulted in higher production, and this does not contradict the single-well sensitivity observations by Kumar et al (2013) and Dahl et al (2014). • This study also showed that much higher cumulative production of oil and gas can be obtained by increasing the vertical height of the fractures.…”
Section: Observationssupporting
confidence: 55%
“…Kumar et al (2013) and Dahl et al (2014) show that hydraulic fracturing and reservoir simulation tools can be used with sensitivity analysis to provide significant insight into expected reservoir responses with different completion technologies and reservoir characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…• eff ective fracture length, • fracture conductivity, • eff ective drainage volume, • optimum fracture spacing, -very low eff ective reservoir permeability; -complex, multi component reservoir systems; -severe vertical heterogeneity; -signifi cant lateral heterogeneity [6].…”
Section: Drilling and Completion Of Unconventional Reservoir Wellsmentioning
confidence: 99%
“…The range of parameters was selected by choosing representative values from the literature (Orangi, 2011;Gong, 2013;Elamin, 2013;Nagarajan, 2013;Kumar, 2013). To confirm with the history match and to maintain simplicity, the reservoir fluid with an initial CGR of 150 STB/MMScf was used for each case.…”
Section: Statistical Study Of the Parametersmentioning
confidence: 99%